Introduction to Educational Game Learning Media through Word Wall at SD Negeri 200118 Padangsidimpuan - Harahap, Lenni Yunita; Hilda, Lelya; Rangkuti, Ahmad Nizar; Nasution, Mariam (Edumaspul: Jurnal Pendidikan, 2023)
The team from the Tadris Mathematics Study Program, Faculty of Tarbiyah and Teacher Training UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan organized community service in the form of training on the use of wordwall applications. This training aims to create interactive learning media. This activity was held at a school that had collaborated with the organizers. This service was held with the aim of providing guidance on the use of the Wordwall application in compiling interactive learning media. This is expected to be a solution to create interesting learning by combining theory and practice.In this activity, participants were given theoretical information about Wordwall through slide presentations from presenters, which were then followed by direct practice by the participants. The result of this training is an increase in teachers' understanding of the latest innovations in the use of interactive learning media. After the training, teachers can apply Wordwall to create teaching materials, learning media, and evaluation tools with their own creativity. Previously, the majority of teachers were not familiar with the theory and practice of using Wordwall, but after training, almost all teachers who participated in this activity were able to understand the theory and apply Wordwall in their learning. The positive impact of this service activity is that teachers can design various educational games with wordwalls according to the material taught, the establishment of cooperation between the service team and the SD Negeri 200118 Padangsidimpuan.